Hierarchical competing inhibition circuits govern motor stability in C. elegans - Yongning Zhang; Yunzhu Shi; Kanghua Zeng; Lili Chen; Shangbang Gao (Nature Communications)
Abstract Stable movement and efficient motor transition are both crucial for animals to navigate their environments, yet the neural principles underlying these abilities are not fully understood. In free-moving Caenorhabditis elegans, sustained forward locomotion is occasionally interrupted by backward movements, which are believed to result from reciprocal inhibition between the interneurons AVB and AVA. Here, we discovered that hierarchical competing inhibition circuits stabilize spontaneous movement and ensure motor transition. We found that the modulatory interneuron PVP activated AVB to maintain forward locomotion while inhibiting AVA to prevent backward movement. Another interneuron, DVC activates AVA and forms a disinhibition circuit that inhibits PVP, thereby relieving PVP’s inhibition of AVA and facilitating backward movement. Notably, these asymmetrical circuit motifs create a higher-order competing inhibition that likely sharpens the motor transition. We also identified cholinergic and glutamatergic synaptic mechanisms underlying these circuits. This study elucidates a key neural principle that controls motor stability in C. elegans.